Sheepdogs - Ackerman, Elliot (Alfred A. Knopf, 2025)
"Skwerl and Cheese are down on their luck. Skwerl, who is resourceful like a squirrel (Marines win battles not spelling bees), used to work for Ground Branch, the CIA's elite paramilitary wing. He was fired after a raid went bad in Afghanistan. Big Cheese Aziz, a legendary pilot-his country's Maverick-is equally hard up. The fall of Kabul has left him grounded, working the nightshift at a gas station. Skwerl recruits Cheese into an anonymous network of so-called sheepdogs, a band of Robin Hoods who operate in the shadowy space between the sheep and the wolves, protecting prey from predator and earning a buck along the way. Their mission, which Skwerl convinces a reluctant Cheese to accept, is to repossess a private jet stranded on a remote African airfield. Their fee: a commission on the jet's $5 million value. But nothing about the job adds up. Their contact goes missing. Their handler is as mysterious as the real source of the money. And when the women in their lives get involved-one pregnant wife and one dominatrix-the stakes skyrocket. From the jungles of Kampala to a glamorous hotel in Marseille, from a veteran-run pizzeria in Kyiv to a Panera in northern Virginia, Skwerl and Cheese and the players around them navigate an increasingly tangled set of loyalties. They join forces with an eccentric bomb technician turned off-the-grid survivalist, a lapsed Amish adventurer, a used car dealer elected to Congress, even a case officer known as the White Russian. Globe-trotting and page-turning, full of heart and humor, Sheepdogs is a uniquely perceptive, wild ride through the underbelly of modern war and intelligence"--